Indirect Standard Time Measurement Using Most Method on Sub Assy Working Model B5581 at Pt. XYZ - Putri, Meylia Vivi (Jurnal Pendidikan Teknologi Informasi dan Vokasional, 2021)
PT XYZ applies a target time for completion of a harness. The problem that will be discussed in this research is how to calculate the standard time and improve the system/work method in order to increase the amount of production of the B5581 sub assy model using the MOST (Maynard Operation Sequence Technique) method. MOST itself is a work measurement technique that is arranged based on a sequence of sub-activity or movement. These sub-activities are basically obtained from movements that have repetitive patterns such as reaching, holding, moving and positioning objects and these patterns are identified and arranged as a sequence of events followed by object movement. Based on the research results, the standard time obtained from data processing for the initial working method is 3.12 minutes/harness and the standard output is 149 harness/day. The standard time can still be reduced again by improving the actual work method, because in the actual work method there are still many transportation activities so that it can waste the operator's work time. After the transportation activities are eliminated, the standard time of the proposed work method is 1.5125 minutes/harness and the standard output is 317 harnesses/day. Keywords: Normal time, MOST, Standard time, Working MethodDOI: http://dx.doi.org/10.23960/jpvti.v3.i1.202109